Isolation of an alkaloid from Anona squamosa Linne - Borja, Maria Isabel A.
An alkaloid can be obtained from Anona squamosal Linne having a maximum absorbance of 246 nm in the UV spectrophotometer. Using thin laer chromatography, it has an Rf value of 0.109 in CHCl3:CH3COCH3 (1:1), 0.94 in CH3COCH3, 0.937 in CHCl3, 0.824 in CHClI3:C2H5OH (2:1) and 0.363 in CHCl3:CH3COOH. Due to the small quantity of alkaloid obtained, there were no crystals collected for further study.